Dinâmica sazonal e espacial da comunidade de aves de um ambiente semiárido - Silva, Clarisse Caroline de Oliveira e (2016)
The semi-arid tropical environments exhibit high seasonality, including wide variation in the rainfall amount throughout the year. This triggers fluctuations in environmental conditions and the resources availability and therefore should influence the variation in species richness of birds in time and space. In this study we used capturerecapture data from birds to evaluate issues such as: (1) species richness vary seasonally with a high change rate, as in other semi-arid; (2) species richness variation is mainly due to the temporary departure of species in the wet-dry transition and return on dry-wet cycle; and (3) the environment with a lower degree of disturbance is associated with less seasonal variation in species composition and richness than higher disturbed environment. The study was carried out in the Caatinga (semi-arid Neotropical) over three years (2012-2015), with two annual capture season (dry and wet) in two environments (natural and disturbed). We analyzed the data through MARK program, with Robust design models and CJS to estimate parameters of the communities’ dynamics (estimates of species input and output (permanent and temporary), species richness and richness change rate). The analysis showed that seasonality and environment are factors decisive for the temporary emigration, the largest output of species in the wet-dry transition and greater input in the dry-wet. We estimate that approximately 40% of the species left the sampling area after the rainy season and 85% of the outside species entered the area before the rainy season. The average of species richness estimated was 33.4 in the dry season and 53.2 in the rainy season. The change rate of species richness varied from 0.6 in the wet-dry transition to 1.5 in the dry-wet, being similar between environments. The estimates of permanent output of species varied from one to three species per transition, while permanent input varied between four and six species per season. Our results showed that the seasonal variation of water regime, as well as the phytophysiognomy change were important factors in determining the community dynamics